Bibliometric Analysis of Impulse Buying Research in the Context of TikTok Shop as E-Commerce (International Journal of Economics and Management Research, 2026)
The development of e-commerce and social media has influenced consumer behavior, creating the phenomenon of impulse buying. TikTok Shop, as a new form of social commerce, has become a medium that encourages spontaneous consumption through various features such as flash sales, live shopping, and algorithmic recommendations. The purpose of this study is to map the scientific landscape related to impulse buying in the digital era using a bibliometric approach. The analysis was conducted on 30 scientific documents from 2020 to 2025, which were visualized through a keyword density map, co-occurrence network, and countries' scientific production and authors. The results show that impulse buying is greatly influenced by psychological factors such as FoMO, impulsiveness, and perceived enjoyment; social factors such as social influence and social commerce; and digital platform factors such as TikTok. Research on this topic has experienced rapid growth with an annual growth rate of 69.52%. This indicates the urgency of this topic in the study of modern consumption behavior. This research contributes to mapping the direction of future research related to impulse buying.